SAT0007 Group 3 innate lymphoid cells numbers in peripheral blood predict ustekinumab (STELARA) therapy responsiveness in psoriatic disease cases with subclinical imaging enthesopathy. (15th June 2017) - El-Sherbiny, YM; Savage, L; Wittmann, M; Emery, P; Goodfield, M; McGonagle, D
Abstract : Background: Ustekinumab 1 targets the common p40 sub-unit of interleukin-12 (IL-12/interleukin-23 (IL-23). In patients treated with Ustekinumab for psoriasis where patients were selected on the basis of subclinical imaging enthesopathy, we have noted an improvement in subclinical imaging enthesopathy (Savage LJ et al submitted), raising the possibility that it may be possible to find a biomarker for predicting response to therapy in psoriatic disease. Innate lymphoid cells may be centrally involved in the pathogenesis of psoriatic skin and joints disease 2, since they express IL-23R receptor and are associated with IL-17/IL-22 production. Objectives: This work was performed to test the hypothesis that peripheral blood ILC perturbations may be useful in defining response in psoriasis cases with imaging confirmed subclinical enthesopathy. Methods: Peripheral blood collected at baseline (before therapy, 24weeks, 54 weeks) from patients in the MUSTEK trial (Ustekinumab in psoriasis cases who had ultrasound imaging confirmed subclinical enthesopathy) (n=23). Cellular immunophenotyping was performed density gradient separated PBMCs. Innate lymphoid cells were identified as lineage negative (CD3- TCRγδ- TCRαβ- CD19- CD14- CD11c- CD1a- CD303- FcɛRI- CD34- CD123-) with positive expression of CD45, CD127. ILC2 cells were identified as Lineage- CD127+ and CRTH2 positive, while ILC3 were identified as Lineage- CD127+, CRTH2 – and CD117 (c-Kit) positive and further subdivided of NKp44+ and NKp44-. ILC1 were identified as lineage- CD127+ CD117-and CRTH2-. For data analysis we separated cases into PASI>90% or PASI <90% responders. The subclinical enthesopathy scores also fell significantly under therapy (Savage LJ data submitted) Results: No correlation was found with total ILCs (ILC1, 2, AND 3) (R=0.104, p=321, Spearman R) and therapy response. While, The absolute numbers of baseline ILC3s was inversely correlated in with the reduction in the PASI score (R -0.404, p=0308, Spearman R). The ILC3s also fell progressively under therapy. All the patients respond with reduction of PASI score mean 92.6% (range 65.8–100%), Interestingly, those patients with reduction below 90% of PASI score has a significantly higher absolute numbers of ILC3+ cells in peripheral blood at the baseline than PASI (n=6/23) than super-responder group (n=17/23) Conclusions: Only peripheral blood ILC3s, but not other ILCs changes, correlate with the PASI score (disease activity), Furthermore, excellent responders (PASI reduction >90%) showed strong correlated with higher ILC3 population at the baseline. This may help to use ILC3 enumeration as predictive parameter for ustekinamab clinical therapeutic response and may be relevant to assessing novel biomarkers for subclincal arthropathy in psoriasis. References: Kreuger et al. N Engl J Med. 2007 Feb 8; 356(6):580–92. Vallinova et al. 2014 Apr;134(4):984–91. Disclosure of Interest: None declared